Making sense of the EU wide stress test: a comparison with the SRISK approach - Timotej Homar; Heinrich Kick; Carmelo Salleo (European Central Bank (ECB), 2016)
We analyse the SRISK measure with respect to its usage as a benchmark for the ECB/EBA 2014 stress test. By regressing the ECB/EBA stress test impact and the SRISK stress impact on a set of factors that are commonly associated with bank credit losses and bank vulnerability, we find that the ECB/EBA stress impact is consistent with findings in the literature on credit losses. In contrast, the SRISK measure bears much less relation to these factors; it is largely driven by the banks' leverage ratio. These differences are deeply rooted in the construction of the respective measures. With its focus on losses to bank equity, the SRISK measure appears poorly matched as a benchmark for the supervisory stress test in Europe, which is centred on losses to banks' total assets.
Keywords: C21; G01; G21; 330; Asset Quality Review; SRISK; stress test evaluation